FAT/CD36-mediated Long-Chain Fatty Acid Uptake in Adipocytes Requires Plasma Membrane Rafts - Pohl, Jürgen (The American Society for Cell Biology, 2005)
We previously reported that lipid rafts are involved in long-chain fatty acid (LCFA) uptake in 3T3-L1 adipocytes. The present data show that LCFA uptake does not depend on caveolae endocytosis because expression of a dominant negative mutant of dynamin had no effect on uptake of [(3)H]oleic acid, whereas it effectively prevented endocytosis of cholera toxin. Isolation of detergent-resistant membranes (DRMs) from 3T3-L1 cell homogenates revealed that FAT/CD36 was expressed in both DRMs and detergent-soluble membranes (DSMs), whereas FATP1 and FATP4 were present only in DSMs but not DRMs. Disruption of lipid rafts by cyclodextrin and specific inhibition of FAT/CD36 by sulfo-N-succinimidyl oleate (SSO) significantly decreased uptake of [(3)H]oleic acid, but simultaneous treatment had no additional or synergistic effects, suggesting that both treatments target the same mechanism. Indeed, subcellular fractionation demonstrated that plasma membrane fatty acid translocase (FAT/CD36) is exclusively located in lipid rafts, whereas intracellular FAT/CD36 cofractionated with DSMs. Binding assays confirmed that [(3)H]SSO predominantly binds to FAT/CD36 within plasma membrane DRMs. In conclusion, our data strongly suggest that FAT/CD36 mediates raft-dependent LCFA uptake. Plasma membrane lipid rafts might control LCFA uptake by regulating surface availability of FAT/CD36.